(untitled) (Washington, DC, 2007)
Guinea-Bissau's productive infrastructure during the past three decades. This situation has contributed to an increase in the degree of vulnerability of the population, especially in rural areas where most economic activities continue to take place. As growth has been weak, poverty levels have remained high. This book provides a collection of papers on conflict, livelihoods, and poverty in Guinea-Bissau, based on both a nationally representative 2002 household survey and a small-scale 2004 survey with both quantitative and qualitative components.